Christmas cards workshop in a Restricted Access Ward - Teresa García; Josefa Marcos (Fundación para el Desarrollo de la Enfermería, 2003)
The Christmas cards workshop is an intervention study made in the Restricted Access Ward (RAW) of Hospital Gregorio Marañón (Madrid), in December 2001, from the 5th to the 22nd. The object of this study was to assess the effectiveness of this workshop to improve the quality of the RAW patients´ hospital day, through their participation. They made 47 cards, the mean per patient was 1,52. Participation: 91,2% of the patients that fulfilled the inclusion criteria. Drawings and texts alluded to the convict´s perspective of Christmas time, from their own experience. The Christmas cards were exhibited in the hospital and they also were sent to different penitentiary institutions in Madrid, to make the RAW known. The course "Education for health for interdisciplinary projects in penitentiary institutions" was the frame of this workshop.